Teaching Islamic perspective of sustainability in landscape design studio - Othman, Jamilah; Mansor, Mazlina; Ahmad Sarkawi, Azila (2011)
This paper presents the techniques of teaching sustainability in the design studio of the first year by integrating the principles of Islam and ecology. The basis to both principles has been clearly defined in the course outline under the Bachelor of Landscape Architecture (BLA) Programme. The pedagogy of the design studio has adopted holistic educational approach (e.g. integration of Islamic and scientific values) as the frameworks to the teaching. Having mentioned that, the authors would like to share their teaching experience in the Department of Landscape Architecture (DoLA), Kulliyyah of Architecture and Environmental Design (KAED), International Islamic University Malaysia (IIUM). The theme of ecology that responds to the concept of sustainable design has been introduced to the students of the second semester. Here, the teaching techniques were divided into three stages. The first stage was associated with knowledge delivery through input lectures and project briefs. The second stage evaluated students’ performance through preliminary studies and design projects. The final stage rectified students’ performance through esquisse projects. In summary, the teaching had the concept of sustainability introduced to the early design studio that may contribute to several implications. Perhaps, it implicates students to execute sustainable design in their study confidently. Importantly, the pedagogy introduced shall produce graduates, whose role as the keepers of the integrity, stability and beauty of an environment is evidently cultured in the practice of LA.